Nanoparticle applications as beneficial oil and gas drilling fluid additives: A review; Journal of Molecular Liquids; Vol. 352 - Al-Shargabi M. Mohammed; Davoodi Sh. Shadfar; Wood D. David; Al-Musai A. Ameen; Rukavishnikov V. S. Valery Sergeevich; Minaev K. M. Konstantin Madestovich (2022, 2022)
Title screen